Equality in Distribution of Human Resources: the Case of Iran's Ministry of Health and Medical Education. - H Mobaraki; A Hassani; T Kashkalani; R Khalilnejad; E Ehsani Chimeh (Tehran University of Medical Sciences, 2013)
Equity in access to and utilization of health services is a common goal of policy-makers in most countries. The fair allocation of human resources is one of the dimensions of equity, which was evaluated in this study.We evaluated the equity of human resources' distribution among Iran's medical science universities between 2005 and 2009 by inequality measures including Lorenze curve, Gini coefficient and Rabin hood indexes.In the distribution 60403 recruitment licenses among medical universities with 72456140 covered populations, Gini coefficient was 0.167 and Robin Hood Index 0.11.Calculations indicated Recruitment licenses are equitably distributed in MOH&ME of Iran. However a portion of recruitment licenses should redistributed for achieving perfect equal distribution among all public medical universities of Iran.